Analysis of the impact of legal circumstances on schizophrenia and bipolar disorder hospitalizations in Portugal: a nationwide study - Gonçalves-Pinho, Manuel (The journal of forensic psychiatry & psychology, 2024)
The main goal of this project was to evaluate the clinical and sociodemographic characteristics of patients hospitalized with schizophrenia or bipolar disorder and the register of legal circumstances. A descriptive study was conducted using a nationwide hospitalization administrative database that contains all admissions registered in public hospitals across mainland Portugal. All discharges between 2008 and 2015 with a primary diagnosis of schizophrenia or bipolar disorder were selected. Legal problems (LP) at the moment of hospitalization were identified based on the presence of a secondary diagnosis of the ICD-9-CM code V62.5 ‘Legal circumstances: Imprisonment; Legal investigation; Litigation; or Prosecution’. A total of 25,835 and 20,807 hospitalizations with a primary diagnosis of schizophrenia and bipolar disorder were analysed, respectively. Approximately 11.8% (n = 3,005) of schizophrenia hospitalizations and 6.0% (n = 1250) of bipolar disorder hospitalizations were associated with registered legal circumstances. Legal circumstances were associated with younger patients, male sex, and a longer length of stay. One in four episodes linked to LP was associated with drug abuse and/or dependence.